Skeletal growth and development dictate the processes of vertebral fracture in the pediatric spine; a review emphasizing fracture biomechanics of the vertebral body during the period of skeletal immaturity - McMorran, John G.; Gregory, Diane E. (Frontiers in Pediatrics, 2025)
Infancy, childhood, and adolescence involve changing body proportions, muscular strength, and the complex processes of skeletal growth, contributing to a unique subset of biomechanical considerations when vertebral fractures result from falls from height, motor vehicle accidents, nonaccidental injuries, and sport and manual labour. In this review, the biomechanics of compression fractures, burst fractures, seatbelt syndrome, nonaccidental trauma, defects of the vertebral endplate, and ring apophysis fractures are all detailed regarding their manifestation in the pediatric spine. Interactions between pediatric diseases, the intervertebral disc, and the spine's facet joints are also briefly discussed, lending additional context toward the unique etiologies of pediatric vertebral fracture. The present narrative review seeks to provide a detailed overview of the key relationships responsible for the unique biomechanical considerations governing vertebral and endplate fracture, in the pediatric population.